2011
DOI: 10.1007/s11999-011-1799-9
|View full text |Cite
|
Sign up to set email alerts
|

Alloprosthetic Composite is a Suitable Reconstruction After Periacetabular Tumor Resection

Abstract: An allograft-prosthetic composite provides a versatile substitution of the pelvis and hip, with functional scores approximately 75% of normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 17 publications
2
69
2
Order By: Relevance
“…In another study, after treatment of deep infection of a hemipelvic prosthesis with implant removal and its substitution with an antibiotic-impregnated bead and spacer, two of three patients achieved healing, however, the third patient underwent an external hemipelvectomy because of persistent infection [36]. In a previous study from our institute concerning pelvic reconstruction with massive allograft, implants were removed in six of eight patients with deep infections [14]. Two of these infections were related to contaminated allografts, which raises the question regarding whether irradiation of the allograft might reduce the risk of infection, even if it might imply an increase of failure risk [34].…”
Section: Discussionmentioning
confidence: 98%
“…In another study, after treatment of deep infection of a hemipelvic prosthesis with implant removal and its substitution with an antibiotic-impregnated bead and spacer, two of three patients achieved healing, however, the third patient underwent an external hemipelvectomy because of persistent infection [36]. In a previous study from our institute concerning pelvic reconstruction with massive allograft, implants were removed in six of eight patients with deep infections [14]. Two of these infections were related to contaminated allografts, which raises the question regarding whether irradiation of the allograft might reduce the risk of infection, even if it might imply an increase of failure risk [34].…”
Section: Discussionmentioning
confidence: 98%
“…This implant is composed of a revision-type prosthesis inserted inside a bone allograft to which the residual abductors and the iliopsoas muscle tendons are biologically reinserted, which should reduce the risk of postoperative dislocation and give better function (Gitelis et al 1988, Zehr et al 1996, Giurea et al 1998, Anract et al 2000, Langlais et al 2003, Farid et al 2006, Biau et al 2008, Donati et al 2008, 2011). In a comparative study on MP and APC, however, Zehr et al (1996) found no differences in function and survival.…”
mentioning
confidence: 99%
“…The main advantages of massive allograft reconstruction are restoration of the pelvic bony architecture, a durable fixation with bony union providing normal biology, and good function in concomitance with a total hip prosthesis. [1][2][3][4] However, high complication rates are associated with allograft reconstruction after pelvic resections. [4][5][6] Infection is one of the most frequent and disastrous complications.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] However, high complication rates are associated with allograft reconstruction after pelvic resections. [4][5][6] Infection is one of the most frequent and disastrous complications. Late-onset infection occurred in our patient at four-year follow-up.…”
Section: Discussionmentioning
confidence: 99%